2017
DOI: 10.24190/issn2564-615x/2017/04.07
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, purification and characterization of water soluble galactomannans from Mimosa pudica seeds

Abstract: Water soluble galactomannans from seed endosperm of Mimosa pudica L. was extracted and characterized (Fig. 1). Nuclear magnetic resonance spectroscopy and Gas Chromatography results revealed the presence of 4-linked mannose backbone with galactose side chains linked at the C6 position. Scanning Electron Micrographs showed smooth, elongated and irregular granular structure of galactomannan. Structural analysis by Attenuated total reflection infrared spectroscopy presented the Mannose to Galactose ratio while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
5
0
2
Order By: Relevance
“…Also the thermal behavior of the isolated polysaccharides strictly depends on the difference in structural and functional groups. The thermal stability of the isolated polysaccharides can be widely used in pharmaceutical industry as an excipient in granule preparation and in food industry as an effective compound for edible film formation (Lavudi et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also the thermal behavior of the isolated polysaccharides strictly depends on the difference in structural and functional groups. The thermal stability of the isolated polysaccharides can be widely used in pharmaceutical industry as an excipient in granule preparation and in food industry as an effective compound for edible film formation (Lavudi et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Also it helps in sustained drug release by entrapment of drug particles in the pores. (Lavudi, Kottapalli, & Goycoolea, 2017).…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…For a better comparison, figure 6 shows the FT-IR spectra of the prepared galactomannan/Zn(OH) 2 -ZnO composite and the extracted and purified galactomannan as a reference (the same that was used for preparing the composite material, and whose main characteristics were reported previously [26]). For the reference case, it is observed that the FT-IR spectrum shows the characteristic bands usually reported in the literature for galactomannan polysaccharides [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. In this way, the broad band at around 3360 cm −1 observed in the reference spectrum corresponds to the O-H stretching vibrations of the hydroxymethyl (-CH 2 OH) The FT-IR spectrum of the galactomannan reference also presents two bands at 1739 and 1645 cm −1 .…”
Section: 1c Ft-ir Spectroscopy Characterizationmentioning
confidence: 94%
“…Galactomannans of Adenanthera pavonia (Ceraqueira et al, 2009) and Mimosa pudica (MP) were extracted, purified and characterized as described in our previous paper (Harikrishna et al, 2017). Work carried out in University of Hyderabad, University of Munster and MVRDL ESIC, Hyderabad, during 2015-2021.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent accompanying paper we have documented the extraction, purification and characteristics of galactomannan sourced from Adenanthera pavonia (Ceraqueira et al, 2009). Also, the galactomannan from Mimosa pudica L. and Dichrostachys cineria L has been studied in our laboratories (Harikrishna et al, 2017;2018) and these legume trees are indigenous to Southern India. In the present study we have investigated the potential applications of these new galactomannans as building blocks of emulsifier, nanoparticles with potential use in pharmacy and food industry.…”
Section: Viscous Behaviour and Interactive Nature Of Indigenous Legum...mentioning
confidence: 99%